2020
DOI: 10.1111/jgh.15084
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the requirement for early surgery in inflammatory bowel disease in the era of biological agents

Abstract: Background and Aim: Biological therapies may be changing the natural history of inflammatory bowel diseases (IBDs), reducing the need for surgical intervention. We aimed to assess whether the availability of anti-TNF agents impacts the need for early surgery in Crohn's disease (CD) and ulcerative colitis (UC). Methods: Retrospective, cohort study of patients diagnosed within a 6-year period before and after the licensing of anti-TNFs (1990-1995 and 2007-2012 for CD; 1995-2000 and 2007-2012 for UC) were identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 19 publications
2
7
0
Order By: Relevance
“…We did not find previous published studies that evaluated the patient journey in terms of UC and overall health care experience for such a long period. Our analysis revealed a progressively worsening disease pattern among UC patients before the initiation of biologics, which is consistent with the relatively low rate of biologic use in UC [12], and may in part help explain why observational studies to date did not find reduced colectomy risk in UC with "early" biologic treatment, despite evidence from clinical trials for reduced hospitalization and surgery with infliximab [14][15][16].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…We did not find previous published studies that evaluated the patient journey in terms of UC and overall health care experience for such a long period. Our analysis revealed a progressively worsening disease pattern among UC patients before the initiation of biologics, which is consistent with the relatively low rate of biologic use in UC [12], and may in part help explain why observational studies to date did not find reduced colectomy risk in UC with "early" biologic treatment, despite evidence from clinical trials for reduced hospitalization and surgery with infliximab [14][15][16].…”
Section: Discussionsupporting
confidence: 78%
“…Biologic use overall is about 44% in CD compared to 16% in UC among commercially insured patients in the US [12]. While this possibly reflects difference in disease progression between CD and UC at least for some patients, it is also possibly related to the lack of real-world evidence in support of early biologic treatment to lower long-term risk of colectomy in UC, despite evidence from clinical trials for reduced hospitalization and surgery with infliximab [13][14][15]. On the other hand, the common practice of delayed biologic treatment in UC would present challenges such as confounding by disease severity to real-world evidence generation.…”
Section: Introductionmentioning
confidence: 99%
“…We did not nd previous published studies that evaluated the patient journey in terms of UC and overall health care experience for such a long period. Our analysis revealed a progressively worsening disease pattern among UC patients before the initiation of biologics, which is consistent with the relatively low rate of biologic use in UC [12], and may in part help explain why observational studies to date did not nd reduced colectomy risk in UC with "early" biologic treatment, despite evidence from clinical trials for reduced hospitalization and surgery with in iximab [14][15][16].…”
Section: Discussionsupporting
confidence: 78%
“…While this possibly re ects difference in disease progression between CD and UC at least for some patients, it is also possibly related to the lack of real-world evidence in support of early biologic treatment to lower long-term risk of colectomy in UC, despite evidence from clinical trials for reduced hospitalization and surgery with in iximab [13][14][15]. On the other hand, the common practice of delayed biologic treatment in UC would present challenges such as confounding by disease severity to real-world evidence generation.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of biologic agents on the rate of IBD-related surgery is also a controversial matter. Several studies reported reductions in surgery rates among IBD patients treated by biologic agents [42][43][44], while others reported no change [20,22,34]. It is important to note that the use of biologic agents in clinical practice involves a greater variability in patient selection, dosing, timing, monitoring, and optimization of therapy.…”
Section: Discussionmentioning
confidence: 99%